Long-term results of tripolar constrained total hip arthroplasty in revision hip arthroplasty: a minimum follow-up of ten years. (June 2019) - El-Husseiny, M.; Masri, B.; Duncan, C.; Garbuz, D. S.
Abstract : Aims: We investigated the long-term performance of the Tripolar Trident acetabular component used for recurrent dislocation in revision total hip arthroplasty. We assessed: 1) rate of re-dislocation; 2) incidence of complications requiring re-operation; and 3) Western Ontario and McMaster Universities osteoarthritis index (WOMAC) pain and functional scores. Patients and Methods: We retrospectively identified 111 patients who had 113 revision tripolar constrained liners between 1994 and 2008. All patients had undergone revision hip arthroplasty before the constrained liner was used: 13 after the first revision, 17 after the second, 38 after the third, and 45 after more than three revisions. A total of 75 hips (73 patients) were treated with Tripolar liners due to recurrent instability with abductor deficiency, In addition, six patients had associated cerebral palsy, four had poliomyelitis, two had multiple sclerosis, two had spina bifida, two had spondyloepiphyseal dysplasia, one had previous reversal of an arthrodesis, and 21 had proximal femoral replacements. The mean age of patients at time of Tripolar insertions was 72 years (53 to 89); there were 69 female patients (two bilateral) and 42 male patients. All patients were followed up for a mean of 15 years (10 to 24). Overall, 55 patients (57 hips) died between April 2011 and February 2018, at a mean of 167 months (122 to 217) following their tripolar liner implantation. We extracted demographics, implant data, rate of dislocations, and incidence of other complications. Results: At ten years, the Kaplan–Meier survivorship for dislocation was 95.6% (95% confidence interval (CI) 90 to 98), with 101 patients at risk. At 20 years, the survivorship for dislocation was 90.6% (95% CI 81.0 to 95.5), with one patient at risk. Eight patients (7.2%) had a dislocation of their constrained liners. At ten years, the survival to any event was 89.4% (95% CI 82 to 93.8), with 96 patients at risk. At 20 years, the survival to any event was 82.5% (95% CI 71.9 to 89.3), with one patient at risk. Five hips (4.4%) had deep infection. Two patients (1.8%) developed dissociated constraining rings with pain but without dislocation, which required re-operation. Two patients (1.8%) had periprosthetic femoral fractures, without dislocation, that were treated by revision stems along with exchange of the well-functioning constrained liners. Conclusion: Constrained tripolar liners used at revision hip arthroplasty provided favourable results in the long term for treatment of recurrent dislocation and for patients at high risk of dislocation. Cite this article: Bone Joint J 2019;101-B(6 Supple B):123–126.